Rapid, landscape scale responses in riparian tundra vegetation to exclusion of small and large mammalian herbivores - Ravolainen, Virve; Bråthen, Kari Anne; Ims, Rolf Anker; Yoccoz, Nigel; Henden, John-André; Killengreen, Siw Turid (Basic and Applied Ecology, 2011)
Productive tundra plant communities composed of a variety of fast growing herbaceous and woody plants are likely to attract mammalian herbivores. Such vegetation is likely to respond to different-sized herbivores more rapidly than currently acknowledged from the tundra. Accentuated by currently changing populations of arctic mammals there is a need to understand impacts of different-sized herbivores on the dynamics of productive tundra plant communities. Here we assess the differential effects of ungulate (reindeer) and small rodent herbivores (voles and lemmings) on high productive tundra vegetation. A spatially extensive exclosure experiment was run for three years on river sediment plains along two river catchments in low-arctic Norway. The river catchments were similar in species pools but differed in species abundance composition of both plants and vertebrate herbivores. Biomass of forbs, deciduous shrubs and silica-poor grasses increased by 40–50% in response to release from herbivory, whereas biomass of silica-rich grasses decreased by 50–75%. Hence both additive and compensatory effects of small rodents and reindeer exclusion caused these significant changes in abundance composition of the plant communities. Changes were also rapid, evident after only one growing season, and are among the fastest and strongest ever documented in Arctic vegetation. The rate of changes indicates a tight link between the dynamics of productive tundra vegetation and both small and large herbivores. Responses were however not spatially consistent, being highly different between the catchments. We conclude that despite similar species pools, variation in plant species abundance and herbivore species dynamics give different prerequisites for change. Produktive Pflanzengemeinschaften der Tundra, die sich aus einer Vielzahl von schnellwüchsigen Kräutern und Gehölzen zusammensetzen, ziehen mit hoher Wahrscheinlichkeit pflanzenfressende Säugetiere an. Eine solche Vegetation reagiert vermutlich schneller auf Herbivore ...